Welfare regimes in the global south: does the capability approach provide an alternative perspective?. (28th February 2019) - Plagerson, Sophie; Patel, Leila
Abstract : Standard definitions and classifications are inadequate to explain current welfare regimes, particularly in the global South. This article explores whether the capability approach can provide an alternative lens for welfare regime analysis. The development of welfare regime theory, and the primary dimensions of analysis are reviewed. The capability approach is critically applied to assumptions underlying comparative welfare regime research, in particular the centrality of institutions. The 'expansion of real freedoms' is proposed as an organising theme for welfare regime analysis across complex and unequal settings. Substantive and methodological limitations in operationalising a capability approach to welfare regime theory are discussed.